Antistaphylococcal Penicillin vs Cefazolin for the Treatment of Methicillin-Susceptible Staphylococcus aureus Spinal Epidural Abscesses. (16th February 2021) - Corsini Campioli, Cristina; Go, John Raymond; Abu Saleh, Omar; Challener, Douglas; Yetmar, Zachary; Osmon, Douglas R
Abstract: Cefazolin is commonly used as an alternative to antistaphylococcal penicillins (ASPs) in treating methicillin-susceptible Staphylococcus aureus (MSSA) infections; however, no study has compared these agents in MSSA spinal epidural abscess (SEA). We describe our experience in managing MSSA SEA and compare the clinical efficacy of cefazolin with ASPs. This retrospective multicenter study reviewed 79 adult patients diagnosed with SEA between January 2006 and July 2020 using data collected from electronic health records and clinical microbiology laboratory databases. Forty-five patients received cefazolin, while 34 received ASPs. The total antibiotic duration was longer in the ASPs group but not statistically significant. There were no significant differences in treatment failure at week 6 vs week 12, 30-day vs overall mortality, or in 90-day recurrence rates between the treatment groups. Cefazolin was equally as effective as ASPs, and our findings suggest that it can be an alternative to ASPs in the treatment of MSSA SEA.